Legal nature of the agreements on the establishment of business entities - Бровченко, Т. І. (Theory and practice of jurisprudence, 2016)
The article covers the kinds and legal nature of the agreements which are entered into by promoters of different commerce companies while establishing such entities. It is zeroed in on various types of promotional agreements concerning the foundation of general partnerships, special partnerships and joint-stock companies. The reasons and kinds of distinctions among stated agreements are also defined in the article as well as those referring to the formation of limited and additional responsibility artificial persons.